PENGARUH VIDEO ANIMASI BERBASIS PROBLEM BASED LEARNING TERHADAP BERPIKIR KREATIF IPAS KELAS V SEKOLAH DASAR - Fadillah Asnah, Nasywa; Pangestu, Deviyanti; Fernando Rizqi, Yoga; Destini, Frida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem of this research is the low creative thinking skills of fifth-grade students in science and natural science at SD Negeri 3 Simbarwaringin. The purpose of this study was to determine the significant effect of the application of animated videos based on problem-based learning on the creative thinking skills of fifth-grade students in science and natural science. This research method used a quasi-experimental design with a non-equivalent control group design. The study population consisted of 33 students. The sampling technique used saturated sampling. Data collection techniques used test and non-test techniques. Data analysis used a independent sample t-test using SPSS 25 calculations. If the significance value is <0.005, then Ho is rejected, meaning significant at 0.003 <0.005. The results of this study indicate a significant effect and difference in the application of animated videos based on problem-based learning on the creative thinking skills of fifth-grade students in science and natural science at SD Negeri 3 Simbarwaringin.